Koch-Priewe, B., Leonhard, T., Pineker, A., Störtländer, J.-C. (Hrsg.) (2013). Portfolio in der LehrerInnenbildung. Konzepte und empirische Befunde. - Kamm, Esther (Swiss Journal of Educational Research, 2018)
Rezension